Democratic frontiers algorithms and society - Filimowicz, Michael (Routledge, 2022)
Democratic Frontiers: Algorithms and Society focuses on digital platforms' effects in societies with respect to key areas such as subjectivity and self-reflection, data and measurement for the common good, public health and accessible datasets, activism in social media and the import/export of AI technologies relative to regime type.